The Miracle of Stem Cell Therapy for Post-Stroke Patients with Type 2 Diabetes - Susanti Vinski, Deby; Cinta Vinski, Natasha (Riviera Publishing, 2024)
The objective of this research is to explain and analyze the miraculous effectiveness of stem cell therapy in treating post-stroke patients, particularly those with diabetes, and to study the consistent properties of this treatment method. The research method employed is a case study that administered stem cell therapy to five post-stroke patients with diabetes, aged between 53 and 72 years. Patient care records, including evaluations and analyses, serve as the primary data source for this study. The stem cells utilized in the therapy are derived from products cultured by the CELLTECH Stem Cell and Banking Laboratory, with processes undergoing thorough quality reviews. The study demonstrates that stem cells have proven to be capable of repairing damaged cells, especially in post-stroke therapy. Some patients undergoing therapy at the CELLTECH Stem Cell Center have successfully recovered and regained the ability to walk. These results are reinforced by a series of laboratory tests confirming their efficacy. Treatments conducted at the Vinski Regenerative Center also show positive research outcomes, enhancing confidence in the clinic's medical services. The implications of this research suggest that stem cell therapy could be an effective method in treating post-stroke patients with diabetes. The positive outcomes of this research could also bolster public trust in medical services provided by stem cell therapy centers such as CELLTECH Stem Cell Center and Vinski Regenerative Center. Further studies and the development of stem cell therapies may open new possibilities in the treatment of post-stroke and related conditions.